Physical-Chemical Characterization of Activated Charcoal from Coconut Shells as an Adsorbent in Reducing Ammonia (NH₃) Content in Nickel Industry Liquid Waste - NIngrum, Resti Ayu; Salawali, Rismul Trianto; Arief, Maipha Deapati; A’Ban, Jamaluddin Gesrianto; Saparullah, Saparullah; Putri, Alfridha Dwi (Jurnal Sains dan Teknik Terapan, 2025)
This research aims to evaluate the effectiveness of activated charcoal produced from coconut shells in reducing ammonia (NH3) levels in domestic wastewater. Liquid waste containing ammonia can cause environmental pollution and negatively impact ecosystems. Therefore, an efficient method is needed to reduce ammonia levels. In this study, activated charcoal was made through the carbonization process of coconut shells and tested for its ability as an adsorbent. The research was conducted experimentally with variations in the mass of activated charcoal of 600 mg, 800 mg, and 1 g. The research results show that coconut shell activated charcoal meets the specifications of Indonesian Industrial Standard (SNI No. 06-3730-1995) with a moisture content of 3%, ash content of 6%, volatile matter content of 14%, and pure activated carbon content of 77%. The reduction in ammonia content obtained was 59.76% for a mass of 600 mg, 61.1% for a mass of 800 mg, and 67.59% for a mass of 1 g. These results indicate that activated coconut shell charcoal has good potential as an adsorbent for the treatment of liquid waste containing ammonia. This research is expected to contribute to the development of more environmentally friendly waste treatment technologies and the sustainable use of local resources.